Persepsi Siswa terhadap Penggunaan Teknologi dalam Pembelajaran Matematika - Amiati, Diah Lara; Yanti, Fitri; Rohman, Rohman; Erviana, Ria; Sepriliani, Sisca Puspita; Cahyani, Lidya (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2025)
Technology is something that can help people worldwide as a means to facilitate education. This study employed a qualitative approach with a descriptive method. The research population consisted of students from grades X, XI, and XII at SMA Negeri 1 Kandis, with a sample of three students from each grade. Data were collected through questionnaires and interviews. The interviews aimed to explore students’ perceptions of the use of technology in mathematics learning at SMA Negeri 1 Kandis, specifically through chat and voice notes (VN) on the WhatsApp application. The interview results were described based on the perception factors applied in this study. The findings showed that the percentage of technology use in mathematics learning was as follows: sometimes 56%, often 28%, always 12%, and never 4%. Thus, it can be concluded that the use of technology in mathematics learning is still very low.